Identify economic indicators (direct and indirect costs) of occupational accidents - RAHMANI, HOSSEIN; LAVASANI, MOHAMMAD REZA MIRI; TEHRANI, MAHHNAZ MIRZA EBRAHIM; LOTFI, FARHAD HOSSEINZADEH (The journal of contemporary issues in business and government, 2021)
The analysis of HSE events, especially occupational accidents, along with identifying the effective factors on the occurrence of accidents is of crucial importance. The study of events before, during and after their occurrence is one of the requirements of study in accidents field. The present study is aimed to manage direct and indirect accident costs and improve the mechanism of accident management based on critical accident costs in the country. The present study is an analytical study that is a cross-sectional case study in different industries of the country. The statistical population of the research includes experts in oil, gas, petrochemical, cement, steel, power plant and road construction and construction, and university professors related to occupational health, industrial safety, HSE, and finally active professors in crisis management and under emergency conditions. 12 people were selected by theoretical saturation method. This research was conducted during 2018 and 2019 in determining the costs of occupational accidents. The research area is in various upstream industries, oil, gas and petrochemical and steel and cement industries and other industrial and urban areas. The research instrument includes a researcher-made questionnaire. Data analysis was performed using fuzzy Delphi method. In the field studies of the study, 8 important and major groups of indicators in occupational accident costs at workplace were identified. In order to calculate and obtain the amount of each of the mentioned indicators, a number of sub- criteria were determined and by examining economic models and calculation software, accident costs and conventional and valid models that had verified validity and reliability showed that 51 sub-indicators in the above 8 groups were effective on calculating the accidents costs. It was found that out of 51 indicators identified in the direct and indirect costs of accidents, 45 indicators have a greater effect and to calculate and technically and economically investigate the accidents costs, 45 indicators were required to be investigated.